Legal Challenges of Artificial Intelligence Implementation in The Tourism Governance System in Bali - Ni Putu Anindya Cahyani (International Journal of Law, Crime and Justice, 2026)
This study analyzes the legal challenges of artificial intelligence (AI) implementation in the tourism governance system in Bali, Indonesia, where the rapid adoption of AI technologies such as smart tourism platforms, automated decision-making systems, and data-driven personalization has transformed tourism services but has not been matched by adequate legal regulation. The research employs a normative legal research method with statutory, conceptual, and comparative approaches, examining Indonesian legal instruments including Law No. 10 of 2009 on Tourism and Law No. 27 of 2022 on Personal Data Protection, alongside comparative frameworks such as the EU Artificial Intelligence Act and Singapore’s Model AI Governance Framework. The analysis uses qualitative descriptive interpretation of legal materials to identify regulatory gaps, legal uncertainties, and governance challenges. The findings reveal that Indonesia lacks a specific and comprehensive legal framework governing AI in tourism, resulting in legal uncertainty particularly in relation to accountability, data protection, ethical governance, and institutional coordination. Comparative analysis indicates that other jurisdictions have adopted more structured, risk-based, and principle-oriented AI governance models that could serve as references for Indonesia’s regulatory development. The study concludes that the absence of AI-specific regulation creates significant challenges for legal certainty and governance effectiveness in Bali’s tourism sector, thereby necessitating regulatory reform to ensure a legal framework that integrates principles of transparency, accountability, fairness, and human oversight in AI-based tourism governance systems.